Polymyxin E–Resistant Gram-Negative Bacteria in Tunisia and Neighboring Countries: Are There Commonalities? - Dziri O; Dziri R; El Salabi AA; Alawami AA; Ksouri R; Chouchani C (Infection and Drug Resistance, 2021)
Olfa Dziri,1– 3 Raoudha Dziri,1 Allaaeddin A El Salabi,4,5 Alhussain A Alawami,4 Riadh Ksouri,6 Chedly Chouchani1– 3 1Laboratory of Microorganisms and Active Biomolecules, Faculty of Sciences of Tunis, University of Tunis El Manar, Tunis, Tunisia; 2Laboratory of Research in Sciences and Technology of Environment, Higher Institute of Sciences and Technologies of Environment of Borj Cédria, University of Carthage, Hammam-Lif, Tunisia; 3Joint Service Unit for Research Genomic Platform, Higher Institute of Environmental Sciences and Technologies of Environment of Borj Cédria, Center of Biotechnology of Borj Cédria, Hammam-Lif, Tunisia; 4Infection Control and Patient Safety Office, New Marwa Hospital, Benghazi, Libya; 5Department of Environmental Health, Faculty of Public Health, University of Benghazi, Benghazi, Libya; 6Laboratory of Aromatic and Medicinal Plants, Center of Biotechnology of Borj Cédria, Hammam-Lif, TunisiaCorrespondence: Chedly Chouchani Email chedly.chouchani@gmail.comAbstract: The current global dissemination of polymyxin E resistance constitutes a real public health threat because of the restricted therapeutic options. This review provides a comprehensive assessment of the epidemiology of polymyxin E–resistant bacteria, with special reference to colistin-resistant Gram-negative bacteria in Tunisia and neighboring countries, based on available published data to January 2020. We aimed to determine their prevalence by species and origin, shedding light on the different genes involved and illustrating their genetic support, genetic environment, and geographic distribution. We found that colistin resistance varies considerably among countries. A majority of the research has focused on Algeria (13 of 32), followed by Tunisia (nine of 32), Egypt (nine of 32), and Libya (one of 32). All these reports showed that colistin-resistant Gram-negative bacteria were dramatically disseminated in these countries, as well as in African wildlife. Moreover, high prevalence of these isolates was recorded from various sources (humans, animals, food products, and natural environments). Colistin resistance was mainly reported among Enterobacteriaceae, particularly Klebsiella pneumoniae and Escherichia coli. It was associated with chromosomal mutations and plasmid-mediated genes (mcr). Four mcr variants (mcr 1, mcr 2, mcr 3, and mcr8), mobilized by several plasmid types (IncHI2, IncP, IncFIB, and IncI2), were detected in these countries and were responsible for their rapid spread. Countrywide dissemination of high-risk clones was also observed, including E. coli ST10 and K. pneumoniae ST101 and ST11. Intensified efforts to raise awareness of antibiotic use and legalization thereon are required in order to monitor and minimize the spread of multidrug-resistant bacteria.Keywords: Gram-negative bacteria, polymyxin E resistance, chromosomal mutations, mcr genes, plasmids